A review of the bird impact process and validation of the SPH impact model for aircraft structures. (1st February 2022) - Guida, M.; Marulo, F.; Belkhelfa, F.Z.; Russo, P.
Abstract: The aim of this paper is to study the phenomenon of bird strike during each phase of the impact and to present a numerical model for its prediction in order to develop the best practices to make a structural component resistant to bird strike. To this end, the Smooth Particle Hydrodynamics (SPH) bird model is developed and validated based on experiments by Barber and Wilbeck and two papers by Guida et al. The experiments considered the impact of small birds on rigid flat panels. Guida et al. developed a 8 lb bird model to predict the impact on a deformable small leading-edge bay and on a full-scale leading edge. The hydrodynamic theory is applied to determine the shock pressure, the shock equation of state, the stagnation pressure and the steady-state equation for water with different porosities. Subsequently, the bird structure is analyzed for different bird geometries and target models. This analysis allowed to design critical components of an aircraft structure, such as the leading edge of the C27J aircraft tail cone in compliance with current aviation airworthiness requirements.